2020
DOI: 10.3390/ijerph17228596
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Relative Age Effect on Competition Performance in Basketball: A Qualitative Systematic Review

Abstract: Performance in basketball is multifactorial. One of the modifying factors is the “Relative Age Effect—RAE”. However, its impact depends on the sample characteristics and sport context. The purpose of this study was to examine the influence of the RAE on basketball competition performance by analysing peer-reviewed articles published until July 2020. According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses systematic search guidelines, nine studies were identified in four databases: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 75 publications
(117 reference statements)
0
23
0
3
Order By: Relevance
“…The franchises have to choose the best players based on their abilities and potential, but must be able to predict the level of future performance. Thus, the selection process (i.e., the NBA Draft) is highly conditioned by the players' performance and favors the selection of those athletes who were born in the first months of the year and that will have a greater impact on the team's performance (De la Rubia et al, 2020a ). In the case of basketball, the presence of the RAE still manifests itself around 20–22 years of age, at the same age category where NBA Draft take place (De la Rubia et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The franchises have to choose the best players based on their abilities and potential, but must be able to predict the level of future performance. Thus, the selection process (i.e., the NBA Draft) is highly conditioned by the players' performance and favors the selection of those athletes who were born in the first months of the year and that will have a greater impact on the team's performance (De la Rubia et al, 2020a ). In the case of basketball, the presence of the RAE still manifests itself around 20–22 years of age, at the same age category where NBA Draft take place (De la Rubia et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the selection process (i.e., the NBA Draft) is highly conditioned by the players' performance and favors the selection of those athletes who were born in the first months of the year and that will have a greater impact on the team's performance (De la Rubia et al, 2020a ). In the case of basketball, the presence of the RAE still manifests itself around 20–22 years of age, at the same age category where NBA Draft take place (De la Rubia et al, 2020a ). Therefore, there may be a ripple effect that benefits the selection of relatively older athletes, despite it still unknown how it affects the long-term performance of the athlete, that is, in his sports career.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In basketball, for instance, height, body mass, running speed, and explosive power are important factors for greater performance [ 15 ], and these can be greatly affected by relative age [ 16 ]. In a systematic review of nine studies, de la Rubia et al [ 17 ] demonstrated that RAEs had a significant impact on basketball performance, particularly within males and at formative ages (14–18 years). Since there appears to be a reliance on advanced physiological and anthropometrical characteristics for greater selection opportunities and performance levels in basketball, these factors may fortuitously exacerbate RAEs in youth settings [ 18 ].…”
Section: Introductionmentioning
confidence: 99%